Analysis of the sustained poor audit outcomes in Mopani District Municipality - Tsepo E. Rangwato; Arthur Shopola; John Molepo (Journal of Local Government Research and Innovation, 2024)
Background: Financial management and accuracy and consistency in reporting remain critical cogs of good governance in South Africa and beyond. The Auditor-General (AG) South Africa, being one of the constitutional instruments responsible for monitoring the consistent application of municipal finance frameworks, has revealed that despite sustained poor audit outcomes in municipal governments, there has been constant disregard for its positive proposals and recommendations for improvement.